Leptin does not Induce an Inflammatory Response in the Murine Placenta - Appel, S.; Turnwald, E-M.; Alejandre-Alcazar, M. A.; Ankerne, J.; Rother, E.; Janoschek, R.; Wohlfarth, M.; Vohlen, C.; Schnare, M.; Meißner, U.; Dötsch, J. (Hormone and Metabolic Research, 2014)
Leptin is described as a pro-inflammatory signal in fat tissue, which is released from adipocytes and in turn activates immune cells. Also, leptin levels are known to be increased in pregnancies complicated with enhanced inflammatory processes in the placenta. Hence, we assumed that increased leptin amounts might contribute to inducing an inflammatory response in the placenta. To test this hypothesis, pregnant mice were continuously infused with recombinant murine leptin s. c. from day g13 to g16, resulting in a 3-fold increase of maternal circulating serum leptin levels. Dissected placentas were examined for the expression of pro-inflammatory cytokines IL-6 and TNF-alpha and the anti-inflammatory cytokine IL-10 using qPCR analysis. No changes were found except for TNF-alpha, which was slightly elevated upon leptin stimulation. However, TNF-alpha protein levels were not significantly higher in placentas from leptin treated mice. Also, leukocyte infiltration in the labyrinth section of placentas was not increased. In summary, our data demonstrate for the first time that elevated leptin levels alone do not induce an inflammatory response in the placenta.
Keywords: placenta; inflammation; leptin